2019
DOI: 10.1098/rspb.2018.2406
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect vaccine and hysteresis

Abstract: Addressing vaccine compliance problems is of particular relevance and significance to public health. Despite resurgence of vaccine-preventable diseases and public awareness of vaccine importance, why is it so challenging to boost population vaccination coverage to desired levels especially in the wake of declining vaccine uptake? To understand this puzzling phenomenon, here we study how social imitation dynamics of vaccination can be impacted by the presence of imperfect vaccine, which only confers partial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 71 publications
0
64
0
1
Order By: Relevance
“…When , , and the model describes a well-mixed society. Although the model is still essentially based on pairwise interactions, dyadic games nonetheless are widely applicable to understanding societal level issues including but not limited to political crises 39 , vaccine compliance 40 , antibiotic resistance 41 , and cultural diversity 42 . Moreover, some argue that simple, transparent models from which insights are readily apparent may be of greater use than more complicated models 43 .…”
Section: Introductionmentioning
confidence: 99%
“…When , , and the model describes a well-mixed society. Although the model is still essentially based on pairwise interactions, dyadic games nonetheless are widely applicable to understanding societal level issues including but not limited to political crises 39 , vaccine compliance 40 , antibiotic resistance 41 , and cultural diversity 42 . Moreover, some argue that simple, transparent models from which insights are readily apparent may be of greater use than more complicated models 43 .…”
Section: Introductionmentioning
confidence: 99%
“…The interest of the physics community was further spurred on by the discovery that scale-free networks provide a unifying framework for the evolution of cooperation [9], and over the past almost two decades, methods of physics have been applied to many contemporary societal challenges [10]. Examples include traffic [11], crime [12], epidemic processes [13], vaccination [14,15], cooperation [16], climate inaction [17], as well as antibiotic overuse [18] and moral behavior [19], to name just some examples.…”
Section: Introductionmentioning
confidence: 99%
“…reduction of overusage of antibiotics, which causes worsening medical cost and mortality especially for life-threatening bacteria infections [72]. Chen et al already showed that hysteresis can appear as an unprecedented roadblock for the recovery of vaccination uptake [73]. Our perceived study may be also useful to understand this puzzling phenomenon too.…”
Section: Discussionmentioning
confidence: 76%